TFEB Promotes Prostate Cancer Progression via Regulating ABCA2-Dependent Lysosomal Biogenesis - Zhu, Xuejin; Zhuo, Yangjia; Wu, Shulin; Chen, Yanfei; Ye, Jianheng; Deng, Yulin; Feng, Yuanfa; Liu, Ren; Cai, Shanghua; Zou, Zhihao; Wang, Bin; Wu, Chin-Lee; et al. (Frontiers in Oncology, 2021)
The interactions of tumor cells and tumor microenvironment (TME) is crucial in prostate cancer (PCa) progression. Transcription Factor EB (TFEB) is a member of the MiT family, which is dysregulated in various cancer and involved in the tumor microenvironment through its specific biologic function. It was reported that downregulation of TFEB induced macrophage polarization in the tumor microenvironment and promotes tumor progression. However, the biological role and clinical significance of TFEB in PCa remain unknown. This study aimed to identify the role of TFEB in PCa and its clinical values. We explored the TFEB expression in PCa by using public databases and verified its prognostic value by IHC, and the results revealed that TFEB expression was up-regulated in PCa tissues and associated with cancer metastasis. Next, we found that overexpression of TFEB promoted PCa cell malignant behavior by a series of in vivo and in vitro experiments. Through RNA-Sequencing and bioinformatics analysis, we found that high expression of TFEB promoted lysosomal biogenesis and knockdown expression of TFEB decreased the number of lysosomes. Furthermore, we identified ATP-binding cassette transporter A2(ABCA2) as a target gene of TFEB and further verified by Cleavage Under Targets and Release Using Nuclease assay and qRT-PCR. Silencing ABCA2 reduced lysosomal biogenesis and decreased matrix metalloproteinase expression for reducing the ability of PCa cell invasion and migration in the tumor microenvironment. Our study suggests that TFEB promotes PCa progression by regulating ABCA2 through lysosomal biogenesis and may serve as a prognostic factor or therapeutic target of PCa.